Development of a validated PROM set for children with tinnitus using the Patient-Reported Outcomes Measurement Information System – Protocol for the ‘Tinnitus in Children’ (TinC) study - Denise Fuchten; Inge Stegeman; Adriana L. Smit (PLoS ONE, 2025)
Introduction Tinnitus in children remains an underexplored area of research, with limited knowledge about its prevalence and impact on daily lives. Current assessments of the impact of tinnitus in children predominantly rely on open-ended questioning during clinical interviews, inconsistent use of structured tools, and data reported by adult proxies. These methods often fail to fully capture the child’s personal experience of tinnitus, underscoring the need for a standardized, child-centered measure to more accurately assess its impact and improve understanding of children’s experience. To address this gap, this study proposes the development of a validated PROM set using the Patient-Reported Outcomes Measurement Information System (PROMIS). Methods The proposed study is a monocenter, mixed-methods, multi-phase observational study. The study will consist of six consecutive steps: (1) identifying patient-important outcomes through focus groups with children aged 8–18 years; (2) defining the underlying constructs of the outcomes and linking them to relevant PROMIS domains; (3) gathering input form an expert panel to refine the outcomes and domains; (4) discussing the PROM set with the focus groups and assess its feasibility; (5) assessing content validity in the expert panel; and (6) assessing the reliability in a sample of children with tinnitus. Discussion By using the generic PROMIS framework to develop a condition-specific measure, the proposed study aims to create a standardized, child-centered PROM set that captures the specific impact of pediatric tinnitus, while maintaining the ability to compare outcomes across different conditions and populations. This PROM set could ultimately be used in both clinical care and research to evaluate tinnitus impact and assess the effects of treatments.